Search for large extra dimensions in the monojet+E(T) channel with the DØ detector. - Abazov, V; Abbott, B; Abdesselam, A; Abolins, M; Abramov, V; Acharya, B; Adams, D; Adams, M; Ahmed, SN; Alexeev, G; Alton, A; Alves, G; et al. (2003)
We present a search for large extra dimensions (ED) in pp collisions at a center-of-mass energy of 1.8 TeV using data collected by the DØ detector at the Fermilab Tevatron in 1994-1996. Data corresponding to 78.8+/-3.9 pb(-1) are examined for events with large missing transverse energy, one high-p(T) jet, and no isolated muons. There is no excess observed beyond expectation from the standard model, and we place lower limits on the fundamental Planck scale of 1.0 and 0.6 TeV for 2 and 7 ED, respectively.